Restoration and conservation of anatomic pieces (2019)
In this study, a restoration process was developed with potassium hydroxide (KOH), in order to improve each of the structures for their posterior fixation, through the use of new methods such as the Chilean conservative fixative solution (SFCCh), with exceptional results. Restore anatomical pieces corresponding to corpse and organs, being these last set with the SFCCh. In this work dealt with processes of restoration with potassium hydroxide, sodium chloride, and sodium hypochlorite, the process began with the cleanliness and suture of the structures for subsequent fixing in Chilean conservative fixative solution, making use of a corpse and different anatomical parts. Work based on items found in the database, Elsevier, Science Direct, ProQuest, and MEDLINE. At the end of the process of restoration and conservation of the anatomical pieces, was observed an improvement in muscle pigment with decrease of rigidity in the specimen, additionally a recovery of appearance in the vascular-nervous elements was achieved. The organs were much more malleable and the structures facilitate the identification of specific details, its subsequent immersion in SFCCh allows the longer preservation of the obtained results. The restoration with potassium hydroxide allows the improvement in the appearance of the different anatomical structures and simultaneously to facilitate its study. The SFCCh is an alternative that replaces partially the use of formaldehyde. In addition, it presents toxicity reduction.